2017
DOI: 10.1088/1361-6668/aa52eb
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of bubbles and improvement of the superconducting properties in MgB2films annealed using electron beam

Abstract: MgB2 superconducting films can be readily obtained using the electron-beam annealing method. However, many bubbles existing in the film severely damage the surface morphology, which is known as the deleterious current-limiting mechanism. Based on morphology images and energy-dispersive spectroscopy spectra, we found that, during the annealing process, solid Mg-rich layers evaporate to form Mg vapour in the precursor film, resulting in bubbles in the film. By reducing the cycle thickness of the precursor film, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The up-limit of local temperature T max in a SEM was also revealed with our experiments on annealing of [Mg-B] N multilayered thin films. The results showed that high-intensity e-beams could induce phase transition in amorphous [Mg-B] N multilayered thin films within 1 s. As a result, an amorphous multilayer was partially turned into a MgB 2 superconducting phase [57]. Figure 3 and Table 2 present some typical results.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The up-limit of local temperature T max in a SEM was also revealed with our experiments on annealing of [Mg-B] N multilayered thin films. The results showed that high-intensity e-beams could induce phase transition in amorphous [Mg-B] N multilayered thin films within 1 s. As a result, an amorphous multilayer was partially turned into a MgB 2 superconducting phase [57]. Figure 3 and Table 2 present some typical results.…”
Section: Resultsmentioning
confidence: 95%
“…For some applications, in e-beam lithography for instance, this e-beam-induced surface heat may cause distortion of designed patterns at the nanoscale in the e-beam writing process, thus resulting in failure of the final devices [13]. In some other applications, the local surface heating effect is utilized for thin film deposition [4], annealing [57], or even sculpting of nanomaterials [8, 9]. Yet to date, precise measurement and evaluation of the local surface temperatures under e-beam irradiation remain as a technical challenge [1012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat dissipation through the substrate of TFTCs has been identified as a serious problem in the thermal probing of local temperature at micro-/nano-scales [ 31 ]. For example, in a transmission electron microscope (TEM) or SEM, a focused electron beam (e-beam) were used to melt metallic thin films or nanowires, or could even vaporize parts of them [ 86 , 87 ], indicating that the local temperature under the focal point of the incident e-beam was higher than the melting points or even vaporization points. However, when a micro-TFTC made on a SiO 2 /Si wafer was placed at the focal point of the incident e-beam, it recorded a much lower temperature.…”
Section: Main Issues Of the Micro-/nano-thin-film Thermocouple Approachmentioning
confidence: 99%
“…A number of techniques were applied for fabrication of practical MgB2 conductors during last 17 years. The chemical doping [8][9][10] , substitution [11,12] , evaporation [13,14] and changing preparation condition [15][16][17] have extensively been used to improve the mechanical, microstructural, superconducting and magnetic properties of the MgB2 material.…”
Section: Introductionmentioning
confidence: 99%